Impact of Climate Change on Food Security in Kenya Using Vector Autoregressive Approach (VAR) - El-Hassanin, Marwa Adel Saad (الجمعية المصرية للاقتصاد السياسي والإحصاء والتشريع, 2016)
This paper aims to practically address two major global challenges climate change and food security in Kenya. Developmental problems such as poverty are already formidable. Climate change is the ultimate risk multiplier, beside the other crises too. Its worst impacts fall on the poor who are least responsible for the problem. Food security issue is getting more attention by world today. The article used Vector Autoregressive approach (VAR) to address the impact of climate change on food security in Kenya. It concludes that CO2- which represents climate change- exerts a negative impact on food security. So, there are significant economic benefits for Kenya in following a low carbon development path, as well as large environmental and social benefits.
Keywords: الأمن الغذائي -- كينيا -- تغير المناخ